Occurrence of antibiotic-resistant Escherichia coli and Salmonella spp. in psittacine birds in selected petting zoos in Klang Valley, Malaysia. - Abu, Jalila; Sem, Ye Fei; Abdul Aziz, Saleha (Malaysian Veterinary Medical Association (MAVMA), 2024)
Today, psittacine birds are gaining popularity in petting zoos for entertainment and educational purposes. However, the birds may be carriers or reservoirs of a number of pathogens which may have zoonotic risk. Therefore, this study was carried out to determine the antibiotic resistance of Escherichia coli and Salmonella spp. in psittacine birds. Fresh faecal samples were collected from 40 apparently healthy birds which had frequent contact with the public in three petting zoos located in Klang Valley area. E. coli was isolated from 15 fresh faecal samples (37.5%) and Salmonella spp. was isolated from 3 (7.5%) of the samples. Salmonellosis and E. coli infection in humans is generally contracted via consumption of contaminated food of animal origin or via contact with animals, environment or manure, thus people touching animals without properly cleaning their hands are at risk of getting infected. Antibiotic susceptibility test was done and 33.3% (5 out of 15) of E. coli isolates were found resistant to Ampicillin; 26.7% (4 out of 15) resistant to Streptomycin; 20% (3 out of 15) resistant to Ciprofloxacin and Tetracycline; 13.3% (2 out of 15) resistant to Chloramphenicol, Nalidixic acid and Sulphonamides; 6.7% (1 out of 15) resistant to Cefotaxime, Ceftiofur, Gentamycin and Norfloxacin. None of the E. coli isolates were found resistant to Amoxicillin/Clavulanic acid. While for Salmonella spp., all of the isolates were resistant to Amoxicillin/Clavulanic acid and Ampicillin, while none were found resistant to Ciprofloxacin, Gentamycin and Norfloxacin. 66.7% of Salmonella isolates (2 out of 3) were resistant to Cefotaxime and Ceftiofur; 33.3% (1 out of 3) resistant to Chloramphenicol, Nalidixic acid, Streptomycin, Sulphonamides and Tetracycline. Multidrug-resistant E. coli was at 20% (3 out of 15) whereas multidrug-resistant Salmonella spp. was 66.7% (2 out of 3). Multidrugresistant E. coli and Salmonella spp. pose a serious threat to the public, as both are capable of causing severe gastroenteritis in humans. Thus, proper precautionary steps should be taken seriously by both the petting zoos and visitors to ensure the bird handlers and visitors are protected.